Fall of the Peacemakers: Austria’s Protestant Nobility and the Advent of the Thirty Years’ War - Thaler, Peter (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
This article examines the prelude to the Thirty Years’ War in Austria. It places the country’s estate system in an international context and evaluates the implications of the religious schism for the relationship between monarchs and nobles. Thwarted in their efforts to enforce confessional orthodoxy in the Holy Roman Empire, the Habsburgs were determined to retain control of their patrimonial lands. The analysis reveals the careful strategy of Catholic restoration pursued by the dynasty as well as the increasing radicalization of Protestant opposition, and the consequential futility of the last major attempt at defusing the confessional conflict in the Habsburg Monarchy. The fundamental differences between noble and dynastic ideologies of state made compromise all but impossible.